MAJOR CHALLENGES AND OBSTACLES FACING DIGITAL REPOSITORIES IN THE DIGITAL ERA - Abdulgaffar, Shahad Ahmed (Acta Scientiae et Intellectus, 2024)
In light of the technological and digital revolution and heavy dependence on digital resources, digital data saving has become a vital means that helps to keep and save intellectual productions. In fact, the digital repositories are one of the most important devices and records that contribute to the perpetuation of intellectual and scientific life. This paper aimed at shedding light on the challenges facing digital repositories, especially in light of the immense and continuous increase of data. It tries to identify those challenges and determine the solutions that can contribute to face them. The lack of independent and detailed studies that tackled the challenges and focused on practical solutions was the reason behind conducting this paper. It targets collecting the related intellectual production and identifying the shortcomings and what is needed to be studied in the future, especially in light of big data and its impact on the continuity and development of digital repositories.